Art In Place: Utilizing Public Art As A Means To Placekeep Public Space In Kansas City’S West Bottoms - Allen, Taylor (Kansas State University, 2017)
Public art is used to accomplish and communicate a wide range of functions within the public realm. This report is about how public art can commemorate place—or ‘placekeep’. Placekeeping is about more than the physical space; it is about commemorating the character, memories, and inherent qualities of a place. Public art is a means to display and communicate this to the public in an aesthetic and physical sense. My individual research on public art explores the topic through the context and work done in collaboration with the Kansas City Design Center (KCDC) on the West Bottoms Reborn studio project which is being done through a grant from the National Endowment for the Arts (NEA). This paper explores the meaning, importance, and ability of public art to commemorate and how it can be utilized to preserve the memory of a place and its people, that in this case, could be lost through rapid development and gentrification in the West Bottoms, Kansas City’s legacy industrial district. Collaboration with the studio, local artists, stakeholders, and community engagement meeting input has provided the means for creating a system of interrelated public spaces that address critical elements to be activated through public art in order to placekeep in the West Bottoms. Placekeeping is KCDC’s proposal for evolving the intents and processes of placemaking to respond to a place that its community deems as a place that does not need to be ‘made’— but rather commemorated or ‘placekept’ (KCDC 2017). Thus, design interventions and public art must identify and enhance these qualities, not try to present a new identity.
Keywords: Public art; Kansas City; Placekeep; West Bottoms